Instrumental, clinical and subjective evaluation of the efficacy of a cosmetic treatment for home use. (19th May 2019) - Ferrillo, Maria; Vastarella, Maria; Cantelli, Mariateresa; Mazzella, Caterina; Fabbrocini, Gabriella
ABSTRACT: Background : In the last few years, there has been increasing demand for aesthetic procedures to improve the effects of skin aging. Aim : To evaluate the anti-aging efficacy, tolerability and skin changes induced by the topical products containing hyaluronic acid, N-acetyl glucosamine and gamma-amino butyric acid through instrumental techniques, clinical and subjective evaluation. Patients/Method : Twenty female enrolled applied a day and night cream after applying a serum, once week applied a mask, for 2 months. A clinical assessment of smoothness, expression wrinkles, fine wrinkles and measurements of the parameters using Reveal Imager, X-Rite, Corneometer, Dermalab, Moisture Meter EpiD were taken at day 0, 15, 30 and 60 of study period. A final assessment questionnaire was submitted. Results : The products were accepted by all the volunteers. The hydration (Corneometer: T0 49.17 vs T60 61.11, average variation 24.28%) (Moisture Meter EpiD: T0 45.73 vs T60 61.10, average variation 33.60%), elasticity (Dermalab: T0 56.06 vs T60 62.78, average variation 11.98%) and lightening of the skin (X-Rite: T0 60.23 vs T60 63.36, average variation 5.26%) improved. All changes were statistically significant ( p < 0.05). Conclusion : The efficacy of the topical products is confirmed by subjective, clinical and instrumental assessment. This should be a routine approach in dermatologic practice.